Investigation of various travelling wave solutions to the extended (2+1)-dimensional quantum ZK equation - Baskonus, Haci Mehmet; Bulut, Hasan; Sulaiman, Tukur Abdulkadir (Springer Heidelberg, 2017)
In this paper, with the aid of the Wolfram Mathematica 9 program, we obtain some novel complex hyperbolic function solutions to the extended (2 + 1)-dimensional quantum Zakharov-Kuznetsov equation by using the sine-Gordon expansion method. We find some complex and hyperbolic function solutions. Subsequently, we plot 2D surfaces representing the obtained solutions by considering some suitable values of the parameters. At the end of this paper, we compare our results with the existing results in the literature by presenting comprehensive conclusions.
Keywords: Exp-Function Method; System; Behaviors